Vancomycin and/or Multidrug-Resistant Citrobacter Freundii Altered the Metabolic Pattern of Soil Microbial Community - Cycoń, Mariusz; Orlewska, Kamila; Markowicz, Anna; Żmijowska, Agnieszka; Smoleń-Dzirba, Joanna; Bratosiewicz-Wąsik, Jolanta; Wąsik, Tomasz J.; Piotrowska-Seget, Zofia (Frontiers in Microbiology, 2018)
Despite many studies, our knowledge on the impact of antibiotics and antibiotic-resistant bacteria on the metabolic activity of soil microbial communities is still limited. To ascertain this impact, the community level physiological profiles (CLPPs) and the activity of selected enzymes (dehydrogenase, urease and phosphatases) in soils treated with vancomycin (VA) and/or multidrug resistant Citrobacter freundii were determined during a 90-day experiment. A multivariate analysis and the resistance (RS)/resilience (RL) concept were used to assess the potential of native microorganisms to maintain their catabolic activity under exposure of VA and/or a high level of C. freundii. In addition, the dissipation rate of VA was evaluated in non-sterile (nsS) and sterile (sS) soils. The results revealed a negative impact of VA on the metabolic activity of soil microorganisms on days 1, 15 and 30 as was showed by a decrease in the values of the CLPP indices (10-69%) and the enzyme activities (6-32%) for treated soils as compared to the control. These observations suggested a low initial resistance of soil microorganisms to VA and/or C. freundii but they were resilient in the long term. Considering the mean values of the RS index, the resistance of measured parameters was categorized in the following order: alkaline phosphatase (0.919) > acid phosphatase (0.899) > dehydrogenase (0.853) > the evenness index (0.840) > urease (0.833) > the Shannon-Wiener index (0.735) > substrate richness (0.485) > the AWCD (0.301). The dissipation process of VA was relatively fast and independent of the concentration used. The DT50 values for VA applied at both concentrations were about 16 days. In addition, the dissipation of VA in nsS was three times faster compared to the dissipation of antibiotic in sS. In conclusion, both CLPP and enzyme activities assays appeared to be useful tool for the determination of disturbances within soil microbial communities and used together may be helpful to understand the changes in their catabolic features. The entry of large quantities of VA and/or C. freundii into soil may temporarily change microbial activity thus pose a potential risk for soil functioning.